1989
DOI: 10.1126/science.2658059
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Catalysts in Organic Synthesis

Abstract: The synthetic value of enzymes is being increasingly recognized. With an understanding of enzyme-catalyzed reactions and the techniques now available for the low-cost production and rational alteration of enzymes and for the design of new enzymatic activities, biocatalytic synthesis should become one of the most valuable synthetic methods. The fundamental as well as the practical issues of this rapidly growing area are described and its impact on the technology pertaining to synthesis is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(51 citation statements)
references
References 103 publications
1
49
0
1
Order By: Relevance
“…The concentrations of acyl donors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), acyl acceptors (a-c), and enzymes were 1 mM, 20 mM, and 5 mM, respectively. The progress of the peptide coupling reaction was monitored by HPLC under the following conditions: isocratic elution at 1 ml/min, 0.1% trifluoroacetic acid/acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of acyl donors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), acyl acceptors (a-c), and enzymes were 1 mM, 20 mM, and 5 mM, respectively. The progress of the peptide coupling reaction was monitored by HPLC under the following conditions: isocratic elution at 1 ml/min, 0.1% trifluoroacetic acid/acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, peptide synthesis using protease-catalyzed reverse reaction has been extensively studied with a variety of amino acids and peptide derivatives as coupling components. [2][3][4][5][6][7][8] It has been reported that the protease-catalyzed peptide synthesis is superior to the chemical coupling method because it is highly stereoselective, racemization-free, and requires less side-chain protection. The major drawback of the enzymatic method, however, is the respective substrate specificity.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15] The protease-catalyzed peptide synthesis is superior to the chemical coupling method. The method requires less-side chain protection than the chemical coupling method.…”
Section: )mentioning
confidence: 99%
“…[1][2][3][4][5][6] In recent years, biocatalytic methodology, once thought to be an esoteric area and largely confined to the laboratories with necessary expertise, has now become a primary activity of research in most of the leading research laboratories working in the areas of both organic, bioorganic and medicinal chemistry. [7][8][9][10][11][12][13][14] Despite the very useful and attractive applications of chemico-enzymatic methodology in synthetic organic chemistry, there still exists some apprehension amongst organic chemists with respect to handling of the enzymes and experimental techniques. Also most of the commercially available enzymes are expensive.…”
Section: Introductionmentioning
confidence: 99%